Penentuan Potensi Ekonomi di Prabumulih dan OKU berdasarkan Indikator Produk Domestik Regional Bruto (PDRB) - Novy Anggraini (Bina Ekonomi, 2017)
The objectives of this research are to know the allocation effect of local economic sectors and to determine the leading economic sectors in Prabumulih and OKU. Data were obtained from sectoral GDRP of Prabumulih, OKU and South Sumatera Province at 2010 Constant Prices from 2010-2014. The methods of analysis used in this research are Location Quotient, Shift Share, and Klassen Typology. The result of allocation effect which has competitive advantages, specialization for Prabumulih are procurement of electricity and gas, construction, wholesale and retail trade, and real estate, while for OKU are agriculture, forestry, and fisheries sectors. The leading sectors for Prabumulih are the procurement of electricity and gas, construction, wholesale and retail trade, financial and insurance services, real estate, company service, education service, also health and social activity services, while for OKU are agriculture, forestry and fishery, education service, health and insurance services, and also other services sectors. Keywords: location quotient analysis, shift share esteban-marquillas analysis, klassen typology analysis, gross regional domestic product